Exploring the impacts of using the artificial intelligence voice-enabled chatbots on customers interactions in the United Arab Emirates - Abdo, Asad; Yusof, Shafiz Mohd (IAES International Journal of Artificial Intelligence (IJ-AI), 2023)
Over the past decade, chatbots have experienced a significant increase in popularity, especially since the outbreak of COVID-19. In the United Arab Emirates, most businesses have accelerated their digital transformation and are relying on chatbots as a primary way to interact with customers. However, many of these chatbots lack a voice input option for customers. This study investigates the benefits and challenges of incorporating artificial intelligence (AI) voice-enabled chatbots into United Arab Emirates (UAE) businesses and how this impacts customer experience. Qualitative research techniques were used to gather information, and the results demonstrate that implementing AI chatbots with voice input and sentiment analysis features can enhance the customer experience by making it more efficient and convenient. Additionally, the study found that AI chatbots can ultimately save businesses time and money, and while they may reduce the need for human agents, they will not replace them entirely. Finally, an implementation framework and suggestions are provided for businesses that are interested in adopting AI voice-enabled chatbots for customer interactions.